Carotid body resection for sympathetic modulation in systolic heart failure: results from first‐in‐man study. (20th September 2016) - Niewinski, Piotr; Janczak, Dariusz; Rucinski, Artur; Tubek, Stanislaw; Engelman, Zoar J.; Piesiak, Pawel; Jazwiec, Przemyslaw; Banasiak, Waldemar; Fudim, Marat; Sobotka, Paul A.; Javaheri, Shahrokh; Hart, Emma C.J.; et al.
Abstract: Aims: Augmented reflex responses from peripheral chemoreceptors, which are mainly localized in the carotid bodies (CBs), characterize patients with systolic heart failure and contribute to adrenergic hyperactivation. We investigated whether surgical resection of CBs in these patients can be performed safely to decrease sympathetic tone. Methods and results: We studied 10 male patients with systolic heart failure (age, 59 ± 3 years; LVEF, 27 ± 7%) who underwent unilateral right‐sided CB resection (four patients) or bilateral CB resection (six patients). Primary endpoints of the study were changes in muscle sympathetic nerve activity (MSNA) and peripheral chemosensitivity measured as ventilatory response to hypoxia from baseline to 1 month post‐CB resection. Safety analysis included analysis of arterial blood gas and oxygenation at night through 2 months post‐procedure and adverse events assessed up to 12 months. At the 1‐month visit, CB resection was associated with a significant decrease both in MSNA (86.6 ± 3.1 vs. 79.7 ± 4.2 bursts/100 beats, P = 0.03) and in peripheral chemosensitivity (1.35 ± 0.19 vs. 0.41 ± 0.17 L/min/SpO2, P = 0.005). It also resulted in improved exercise tolerance. Amongst some patients with bilateral CB resection, there was a trend towards worsening of oxygen saturation at night, which in one case required therapy with non‐invasive ventilation. Conclusion: We present first‐in‐man evidence that CB resection in patients with systolic heart failure is associated with a decrease in sympathetic activity. A bilateral procedure may carry a risk of worsening oxygenation at night. CB modulation constitutes an interesting research avenue, but careful consideration of the balance between safety and efficacy is necessary before further clinical trials.